Pengaruh Strategi Segmenting, Targeting Dan Positioning Terhadap Keputusan Pembelian Produk Erigo (Studi Kasus Pada Mahasiswa Universitas Merdeka Pasuruan) - Siska Dewi Apriliyanti; Ratna Pudyaningsih; Vita Fibriyani (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
Currently, we see many local brands from Indonesia starting to appear on the market both at home and abroad. The success of this local brand with the right marketing strategy. One of the local brands that has succeeded in penetrating foreign markets is Erigo. This study aims to determine the effect of segmenting, targeting and positioning strategies on purchasing decisions for Erigo products for students at Merdeka University, Pasuruan. The population used is active students at Merdeka University, Pasuruan in 2022 with a sample of 92 students and uses a purposive sample with age criteria of 17 to 45 years, consumers who have purchased and know Erigo products. The data analysis used in this research is multiple linear regression. The results showed that segmenting, targeting and positioning simultaneously had a positive and significant effect on purchasing decisions for Erigo products with an F count of 31.978 > F table of 2.71 and a significance value of 0.000 <0.05. Meanwhile, partially segmenting shows a significant influence on purchasing decisions with a significance value of 0.044 <0.05 and has t count 2.044 > t table 1.986. Targeting also partially shows a significant influence on purchasing decisions with a significance value of 0.000 <0.05, it is known that the t count value is 5.184 > t table 1.986. Partially positioning shows a significant influence on purchasing decisions with a significance value of 0.012 <0.05 and has t count 2.578 > from t table 1.986. The most dominant variable is targeting with an influence on the purchasing decision variable of 31%.